2022
DOI: 10.3390/su142114237
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Ambidexterity as an Outcome of Quality Dimensions and Triple Helix: The Role of Technology Readiness and User Satisfaction

Abstract: Advancing times and rapidly developing technology put pressure and responsibility on the management of organizations. Organizational ambidexterity is a concept for an organization that can balance profitability with innovation and development. This study examined the relationship between the triple helix and quality dimensions on organizational ambidexterity mediated by technology readiness and user satisfaction to give management an advantage in addressing this problem. Quantitative analysis methods using PLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Organizational ambidexterity refers to an organization's ability in the form of exploration and exploitation-to compete in mature technologies and markets where efficiency, control, and incremental improvement are valued and compete in new technologies and markets where flexibility, autonomy, and experimentation are required (Prasetio et al, 2022). The word Ambidexterity means "extraordinary prowess," just like the ability to use both hands equally well.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Organizational ambidexterity refers to an organization's ability in the form of exploration and exploitation-to compete in mature technologies and markets where efficiency, control, and incremental improvement are valued and compete in new technologies and markets where flexibility, autonomy, and experimentation are required (Prasetio et al, 2022). The word Ambidexterity means "extraordinary prowess," just like the ability to use both hands equally well.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The operational definition of the research variables is explained as follows: Technology readiness is defined as the level of readiness of the organization and employees towards the use of technology [17]. AO is the ability of an organization to balance organizational exploration and exploitation in the introduction of new technology with the preservation of existing technology [12]. EC is the ability of employees to explore ideas with problemsolving methods adopted and refined from previous research [18].…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…Technology readiness should not be overlooked when evaluating client acceptance of technology-enabled services. Its function must be explained and incorporated into any model of technology acceptance, particularly in industrial innovation and organizational ambidexterity [12].In the research, [12], The result showed that technology readiness influences organizational ambidexterity both directly and moderately.…”
Section: Introductionmentioning
confidence: 98%